Mapping the Scientific Research on Suicide and Physical Activity: A Bibliometric Analysis - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This research provides an overview of the current state of scientific literature related to suicide and physical activity (PA). A bibliometric analysis of studies published between 1996 and 2022 in The Web of Science (WoS) was carried out, applying the traditional bibliometric laws, using Microsoft Excel and the VOSviewer software for data and metadata processing. A total of 368 documents (349 primary research and 19 reviews) were extracted from 70 WoS categories. The results revealed an exponential increase in scientific production from 2017 to 2022 (R2 = 88%), revealing the United States hegemony being the most productive country, with 156 of the publications (42.4%), the most cited (4181 citations) being the centre of a collaborative network with links to 35 countries and having April Smith, from the Miami University, as the most prolific author (eight publications) and Thomas Joiner, from the Florida State University, as the most cited author (513 citations). The Psychiatry WoS category, with 155 papers, had the highest number of publications, and The Journal of Affective Disorders, from Elsevier, had the highest number of published papers within this category. © 2022 by the authors.